Advances in lung bioengineering: Where we are, where we need to go, and how to get there - Hsiung, Tiffany; James, Les; Chang, Stephanie H.; Geraci, Travis C.; Angel, Luis F.; Chan, Justin C. Y. (Frontiers in Transplantation, 2023)
Lung transplantation is the only potentially curative treatment for end-stage lung failure and successfully improves both long-term survival and quality of life. However, lung transplantation is limited by the shortage of suitable donor lungs. This discrepancy in organ supply and demand has prompted researchers to seek alternative therapies for end-stage lung failure. Tissue engineering (bioengineering) organs has become an attractive and promising avenue of research, allowing for the customized production of organs on demand, with potentially perfect biocompatibility. While breakthroughs in tissue engineering have shown feasibility in practice, they have also uncovered challenges in solid organ applications due to the need not only for structural support, but vascular membrane integrity and gas exchange. This requires a complex engineered interaction of multiple cell types in precise anatomical locations. In this article, we discuss the process of creating bioengineered lungs and the challenges inherent therein. We summarize the relevant literature for selecting appropriate lung scaffolds, creating decellularization protocols, and using bioreactors. The development of completely artificial lung substitutes will also be reviewed. Lastly, we describe the state of current research, as well as future studies required for bioengineered lungs to become a realistic therapeutic modality for end-stage lung disease. Applications of bioengineering may allow for earlier intervention in end-stage lung disease and have the potential to not only halt organ failure, but also significantly reverse disease progression.